Functionalized Mesoporous Silica Utilization for VOCs Adsorption - C W. Purnomo; S. Z. Qiao (ASEAN Journal of Chemical Engineering, 2007)
Functionalized FDU-12 has been studied in the application for hydrocarbon vapor adsorption. In here, the moieties were phenyl and vinyl which being introduced into FDU-12 synthesis using co-condensation methods with the presence of tri block co-polymer P123 as the template. The adsorption used two different vapors, benzene and n-hexane, at 200C. The result suggested that the groups increased the affinity of adsorbing the vapors compared with pure FDU-12.